Senior Co-Housing in the Netherlands: Benefits and Drawbacks for Its Residents - Rusinovic, Katja (Int J Environ Res Public Health, 2019)
Senior co-housing communities offer an in-between solution for older people who do not want to live in an institutional setting but prefer the company of their age peers. Residents of co-housing communities live in their own apartments but undertake activities together and support one another. This paper adds to the literature by scrutinizing the benefits and drawbacks of senior co-housing, with special focus on the forms and limits of social support and the implications for the experience of loneliness. Qualitative fieldwork was conducted in eight co-housing communities in the Netherlands, consisting of document analysis, interviews, focus groups, and observations. The research shows that co-housing communities offer social contacts, social control, and instrumental and emotional support. Residents set boundaries regarding the frequency and intensity of support. The provided support partly relieves residents’ adult children from caregiving duties but does not substitute formal and informal care. Due to their access to contacts and support, few residents experience social loneliness. Co-housing communities can potentially also alleviate emotional loneliness, but currently, this happens to a limited degree. The paper concludes with practical recommendations for enhancing the benefits and reducing the drawbacks of senior co-housing.